Empowering Teachers' Digital Literacy: Training on Creating Digital Learning Media at Rural Elementary School - Lilis Supratman; Aip Muhamad Irfan; Annisa Nurramadhani; Radita Dwi Ningsih; Krizza Mae Raposas Pomares (FKIP UNIVERSITAS PAKUAN, 2025)
Digital learning media play a crucial role in facilitating the transfer of knowledge, particularly in helping students understand abstract concepts. In response to the growing need for technological integration in education, a community service program aims to train teachers in the effective use of digital tool for developing instructional media. This program involved eight teachers at rural elementary school and aimed to enhance their competence, motivation, and consistency in producing digital learning resources. The initiative aligns with the goals of sustainable development goal 4, focuses on improving the quality of education. The activity employed a participatory training and mentoring approach, comprising two key phases: the initial training sessions and subsequent mentoring. The program began with a needs assessment survey administered to participating teachers to understand their prior knowledge and skills. Following this, structured training sessions were conducted, and teachers were guided in the creation of digital learning products. These products were then evaluated and refined through mentoring to ensure their pedagogical quality and relevance. The effectiveness of the program was measured quantitatively using a questionnaire, focusing on four key indicators: basic digital skills, operational competence, motivation to create digital materials, and consistency in their development. The results showed an improvemen across all indicators, demonstrating a strong shift toward digital adoption. Sustained progress requires comprehensive support through institutional policies. It can be concluded that empowering teacher digital literacy could enhance their digital skills.